PENGARUH PARTISIPASI ANGGARAN TERHADAP SENJANGAN ANGGARAN DENGAN ASIMETRI INFORMASI, KOMITMEN ORGANISASI DAN PENEKANAN ANGGARAN SEBAGAI VARIABEL MODERASI (Studi Pada OPD Kabupaten Kampar dan Kota Pekanbaru) - Cici Lestari; Raja Adri Setiawan Surya; Nanda Fito Mela (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aims to examine : 1) the effect of budgetary participation on budgetary slack, 2) the effect of budgetary participation on budgetary slack with information asymmetry as moderating variable, 3) the effect of budgetary participation on budgetary slack with organizational commitment as moderating variable, and 4) the effect of budgetary participation on budgetary slack with budget emphasis as moderating variables. The population in this study was 47 OPD KamparRegency and pekanbaru city. In this study, the sample used is the 132 respondents were selected using purposive sampling method. This study used primary data by dissemination of the questionnaires. Technical analysis for test hypothesis that used in this study are simple regression analysis and Moderated Regression Analysis (MRA). The analytical tool used in this study was Ststistical Product and Service Solution (SPSS) version 22.0. The result of this research showed that : 1) budgetary participation significant effect on the budgetary slack with significant level of 0.000, 2) information asymmetry can be moderate the effect of budgetary participation on budgetary slack with significant level of 0.000, 3) organizational commitment can be moderate the effect of budgetary participation on budgetary slack with significant level of 0.000, and 4) budget emphasis can be moderate the effect of budgetary participation on budgetary slack with significant level of 0,001.Keyword : participation, asymmetry, commitment, emphasis and slack